Interleukin-6 receptor blocking with intravenous tocilizumab in COVID-19 severe acute respiratory distress syndrome: A retrospective case-control survival analysis of 128 patients. Issue 114 (November 2020) - Canziani, Lorenzo M.; Trovati, Serena; Brunetta, Enrico; Testa, Amidio; De Santis, Maria; Bombardieri, Emilio; Guidelli, Giacomo; Albano, Giovanni; Folci, Marco; Squadroni, Michela; Beretta, Giordano D.; Ciccarelli, Michele; et al.
Abstract: In cases of COVID-19 acute respiratory distress syndrome, an excessive host inflammatory response has been reported, with elevated serum interleukin-6 levels. In this multicenter retrospective cohort study we included adult patients with COVID-19, need of respiratory support, and elevated C-reactive protein who received intravenous tocilizumab in addition to standard of care. Control patients not receiving tocilizumab were matched for sex, age and respiratory support. We selected survival as the primary endpoint, along with need for invasive ventilation, thrombosis, hemorrhage, and infections as secondary endpoints at 30 days. We included 64 patients with COVID-19 in the tocilizumab group and 64 matched controls. At baseline the tocilizumab group had longer symptom duration (13 ± 5 vs. 9 ± 5 days) and received hydroxychloroquine more often than controls (100% vs. 81%). The mortality rate was similar between groups (27% with tocilizumab vs. 38%) and at multivariable analysis risk of death was not significantly influenced by tocilizumab (hazard ratio 0.61, 95% confidence interval 0.33–1.15), while being associated with the use at baseline of non invasive mechanical or invasive ventilation, and the presence of comorbidities. Among secondary outcomes, tocilizumab was associated with a lower probability of requiring invasive ventilation (hazard ratio 0.36, 95% confidence interval 0.16–0.83; P = 0.017) but not with the risk of thrombosis, bleeding, or infections. The use of intravenous tocilizumab was not associated with changes in 30-day mortality in patients with COVID-19 severe respiratory impairment. Among the secondary outcomes there was less use of invasive ventilation in the tocilizumab group. Highlights: Survival in ARDS from COVID-19 is significantly associated with age and comorbidities. The use of tocilizumab is not associated with difference in 30-day mortality. Patients treated with tocilizumab require invasive ventilation significantly less frequently than controls. No clear effect of tocilizumab was measured also on secondary outcome such as bleeding, thrombosis or infections. In patients with a survival exceeding 5 days, tocilizumab is associated with a significantly better survival.